2015
DOI: 10.1007/s10554-015-0656-4
|View full text |Cite
|
Sign up to set email alerts
|

Hand-held echocardiography in the setting of pre-operative cardiac evaluation of patients undergoing non-cardiac surgery: results from a randomized pilot study

Abstract: Transthoracic echocardiography is not a routine test in the pre-operative cardiac evaluation of patients undergoing non-cardiac surgery but may be considered in those with known heart failure and valvular heart disease or complaining cardiac symptoms. In this setting, hand-held echocardiography (HHE) could find a potential application as an alternative to standard echocardiography in selected patients; however, its utility in this context has not been investigated. The aim of this pilot study was to evaluate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 26 publications
0
9
0
1
Order By: Relevance
“…By comparing the use of the ultraportable cardiac US (Opti-Go Philips) with the conventional echocardiography (Philips iE33), the investigators found the same rate of diagnostic conclusiveness between the techniques, although the former is faster and promotes a less waiting time, which optimizes the preoperative evaluation. 18 In this study, 211 patients without suspicion of heart diseases and previously approved for surgeries were studied, which may explain the higher percentages of tests without significant changes in our sample (60.7% versus 12.8%). In the Italian study, 18 patients were randomized to one of two techniques, and 50 patients underwent the ultraportable cardiac US, whereas in our study, all patients underwent this technique.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…By comparing the use of the ultraportable cardiac US (Opti-Go Philips) with the conventional echocardiography (Philips iE33), the investigators found the same rate of diagnostic conclusiveness between the techniques, although the former is faster and promotes a less waiting time, which optimizes the preoperative evaluation. 18 In this study, 211 patients without suspicion of heart diseases and previously approved for surgeries were studied, which may explain the higher percentages of tests without significant changes in our sample (60.7% versus 12.8%). In the Italian study, 18 patients were randomized to one of two techniques, and 50 patients underwent the ultraportable cardiac US, whereas in our study, all patients underwent this technique.…”
Section: Discussionmentioning
confidence: 85%
“…18 In this study, 211 patients without suspicion of heart diseases and previously approved for surgeries were studied, which may explain the higher percentages of tests without significant changes in our sample (60.7% versus 12.8%). In the Italian study, 18 patients were randomized to one of two techniques, and 50 patients underwent the ultraportable cardiac US, whereas in our study, all patients underwent this technique.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Hand-held echocardiography could be considered an alternative to standard echocardiography in the pre-operative evaluation of patients undergoing non-cardiac surgery. Cavalli et al [20] compared standard echo to bedside evaluation with a pocket-size imaging device in 100 patients scheduled for non-cardiac surgery. H and-held echo pro-patients with acute Mi.…”
Section: Hand-held Echocardiography For Pre-operative Evaluationmentioning
confidence: 99%
“…It also provides information on ventricular dysfunction, valvular disease, and regional wall motion abnormality. [6][7][8] However, clinical evidence regarding the utility of preoperative echocardiography in non-cardiac surgery is limited. There is no recommendation for the use of echocardiography, except for high-risk vascular procedures in patients with reduced functional capacity.…”
mentioning
confidence: 99%